2013
DOI: 10.1007/s11999-013-2801-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Bone Formation About the Hip Undergoes Endochondral Ossification: A Rabbit Model

Abstract: Background Heterotopic ossification (HO) occurs most commonly after trauma and surgery about the hip and may compromise subsequent function. Currently available animal models describing the cellular progression of HO are based on exogenous osteogenic induction agents and may not reflect the processes following trauma.Questions/purposes We therefore sought to characterize the histologic progression of heterotopic bone formation in an animal model that recapitulates the human condition without the addition of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Similar to normal fracture healing, HO is believed to develop through an endochondral intermediary [4,5]. Metabolic derangements, including diabetes, can result in decreased bone mineral density and impaired fracture site healing in normal bone [6][7][8].…”
mentioning
confidence: 99%
“…Similar to normal fracture healing, HO is believed to develop through an endochondral intermediary [4,5]. Metabolic derangements, including diabetes, can result in decreased bone mineral density and impaired fracture site healing in normal bone [6][7][8].…”
mentioning
confidence: 99%
“…It has been shown that there is upregulation in key osteogenic and chondrogenic gene transcripts (BMP2, BMP3, ALPL, COLL2A1, COLL10A1, COLL11A1, COMP, CSF2, CSF3, MMP8, MMP9, SMAD1, and VEGFA) in the soft tissues of high‐energy combat wounds . The upregulation of these gene transcripts suggests an endochondral (as opposed to an intramembranous) model of development of acquired HO, something that has been confirmed separately in an animal model …”
Section: Genetic Forms Of Homentioning
confidence: 86%
“…Among the risk and predisposing factors summarized from clinical data, spreading bone marrow to the surgical field during reaming femoral canal was speculated [13] . This theory is supported by an animal study, in which HO was successfully induced in rabbits by surgical reaming of femoral medullary canal and intentionally leaving bone debris and marrow materials in the wound [14] . Bone marrow is well-known for containing mesenchymal stem cells (MSCs) and other osteogenic elements [15] .…”
Section: Introductionmentioning
confidence: 85%